Characterising recovery from renal transplantation and live-related donation using cardiopulmonary exercise testing. Issue 12 (5th June 2021) - Angell, Johanna; Dodds, Nicholas; Darweish-Mednuik, Alia M; Lewis, Simon; Pyke, Mark; Mitchell, David C; Hamilton, Kay; White, Paul; Tolchard, Stephen
Abstract: Background: An association between end-stage renal failure and exercise intolerance exists. Whether live kidney donation impacts on exercise tolerance is unknown. Here recovery post renal transplant and donation using cardiopulmonary exercise testing is investigated. Methods: Renal donors ( n = 28) and recipients ( n = 24) undertook a cardiopulmonary exercise test, Duke activity score index and patient reported health score questionnaires pre-operatively and in the 7th and 14th week post-operatively. Anaerobic threshold, peak oxygen uptake and ventilatory equivalents were measured in relation to activity and reported health scores. Haemoglobin and renal function was recorded. Results: Recipients showed impaired cardiopulmonary function compared to donors with lower anaerobic threshold (10.5 vs. 14.4 ml/kg/min) and peak oxygen uptake (18.5 vs 23.0 ml/kg/min). Post-operatively the anaerobic threshold of recipients improved and normalised by the 14th week, whereas that in donors fell by ∼20% by the 7th (mean 11.4 ml/kg/min), recovering by the 14th (mean 15.6 ml/kg/min). Reported health but not activity scores showed similar changes. Conclusions: Recovery following renal transplantation and donation differ. Transplantation improves renal function resulting in an increase in anaerobic threshold and peak oxygen uptake which essentially normalise by the 14th week post-operatively. Donors suffer a 20% reduction in cardiopulmonary reserve post-operatively, which recovers by the 14th week, suggesting no associated chronic exercise intolerance. IMPLICATIONS FOR REHABILITATION: Cardiopulmonary exercise testing is a real-time predictor of functional capacity and thus is used as a pre-operative tool to measure physiological fitness and predict outcomes. Renal failure is associated with exercise intolerance and transplantation is transformational in terms of quality of life, longevity and healthcare cost. Live – related renal donation is increasingly available but whether donation itself carries a long-term health burden has not been previously well established. This study suggests that renal donation is not associated with long-term cardiopulmonary compromise and patients who donate their kidneys recover their previous fitness within 14 weeks.